Aplikativni vidik otrokovega pripovedovanja v predšolskem obdobju - Baloh, Barbara (Revija za elementarno izobraževanje, 2015)
Applicative Aspect of Child’s Narration in Preschool Period. By narrating, the child communicates his experience, gained either on his own or mediated to him by someone else. This is how children extend their narrative textual world and build their narrative scheme as a means of further narrative text composition. Taking into consideration the importance of narration in the curriculum, we are faced with the question how it would be possible to properly encourage narration, which is the child’s natural need, and how to further develop it according to the child’s age. The paper introduces curricular problems concerning the role of the adult (preschool teacher/teacher) in narration and narration as a culturally based activity, which is extremely important for child’s literacy